SOFT SKILLS YANG DIBUTUHKAN TENAGA KERJA PADA USAHA JASA KONSTRUKSI DI KOTA PADANG - 309-313 , Laras Oktavia Andreas (Universitas Negeri Padang, 2014)
ABSTRACT Lack of knowledge labour concerning ability of soft skills, representing a problems exist in effort construction service in Padang town. manpower can only use skills techniques but do not have good soft skills to get in touch with co-workers or leaders. to examine the components of soft skills require to conduct of research with aim to know soft skills which is all important to be owned by labour of effort construction service in Padang Town. This research is done in the service campany gred 6 and gred 7 with a total sample of 16 companies. Type and data source is data sekunder in the form member data of Gapensi Padang town and primary data steming from passed to kuesioner is company head. Technique data collecting use enquette with scale of likert, technique analyse data use descriptive analysis. Result of this research showing that from 19 statement item obtained by 16 of soft skills is including into category of vital importance, that is of initiative, ethics/integrity, of critical thinks, can be pledged, of oral communications, creative, analytical, of x'self management, solving problem, flexible, of job in team, self-supporting, listen, taft, of have logical argument, of time management, and 3 statement of soft skills is including at important category, that is of willingness learn, of motivation, have co’operation. Keyword: Soft Skills, Labour, Effort Service Construction.